Situational predictive modelling of the flood hazard in the Dniester river valley near the town of Halych - Stefanyshyn, Dmytro V.; Korbutiak, Vasyl M.; Stefanyshyna-Gavryliuk, Yulija D. (Kyiv National University of Construction and Architecture, 2019)
There has been presented a method of situational predictive modelling of the flood hazard in the Dniester River valley near the town of Halych based of hydrological observations data obtained at the Halych water level gauge. Some features in the behaviour of the equation of relationship between levels and water discharges for the Halych water level gauge were revealed, in particularly, regularities fostering reliable forecasting the flood hazard by means of statistical data and ambiguities interfering similar predicting. The possibility of effective situational predicting of the flood hazard according to current data of hydrological observations to minimize probable harm and losses was shown.